The Relationship of Readiness for Independent Learning to Attitude and Cognitive Values in Tutorial Learning for Students of the Faculty of Medicine, University of Muhammadiyah North Sumatra - Faudhiah, Nurul; Isnayanti, Desi (Buletin Farmatera, 2025)
Abstract: Problem Base Learning (PBL) is a learning strategy that emphasizes learning on students or in other words student-centered learning. Tutorials are a manifestation of the implementation of the PBL program. Student independence is the principle of tutorial activities. Tutorial group discussions cause interaction between students and it is expected that the active learning process will occur. Student assessments in tutorials are based on attitude and cognition. Objective: To find out the relationship between the readiness of independent learning and students in the tutorial, namely attitude and cognitive  values in students of the Faculty of Medicine, University of Muhammadiyah North Sumatra. Methods: This study uses an analytical descriptive research method with a cutting-edge approach. The research population is students Faculty of Medicine, University of Muhammadiyah North Sumatra class of 2021 which totals 274 people. The sampling technique used simple random sampling (random sample) by drawing lots to find 83 people, the sample size used a categorical correlation formula with an addition of 10% to avoid a shortage of samples in the event of a drop out, which was 83 respondents. Results: The overview of the distribution  of attitude  values shows that the most dominant score is very satisfactory (score 85-100) as many as 63 people (75.9%). The overview of the cognitive value of the tutorial shows that 45 people (55.4%) have unsatisfactory scores (55 – 69). Readiness for independent learning had no relationship with the attitude tutorial score, which was 0.209 (p 0.05). Readiness for independent learning had no relationship with the cognitive value of tutorials, which was 0.645 (p 0.05). Conclusion: the readiness of independent learning has no relationship with   the attitude and cognitive values of students of the Faculty of Medicine, University of Muhammadiyah North Sumatra in the tutorial process.